Development of E-Magnetic Learning Media Based on Smart Apps Creator (SAC) on Topic of Magnetism - Nurafni Dg. Palari; Mursalin Mursalin; Nova Elysia Ntobuo; Tirtawaty Abdjul; Dewi Diana Paramata; I Made Hermanto (Jurnal Ilmiah Profesi Pendidikan, 2025)
This research aims to produce e-magnetic learning media products based on the Smart Apps Creator (SAC) application on magnetic material that meets quality criteria regarding validity, practicality, and effectiveness. This type of research is Research and Development (R&D) using the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development model. The research subjects were 21 students in class IX-C of SMP Negeri 11 Gorontalo, Gorontalo Regency, Gorontalo Province. The research results show that (1) the validation results of e-magnetic learning media based on SAC by two validators obtained an average validation score of 96.88%, meeting the criteria of being valid and usable; (2) The practical aspect shows that observations of learning implementation obtained an average percentage of 88% with very good criteria and student responses obtained an average percentage of 9% with very good criteria. The results obtained indicate that the e-magnetic learning media based on SAC that was developed is practical; and (3) The effectiveness aspect is determined through student activity, which reached 84.42% with very good criteria and learning outcomes for the cognitive domain in magnetism topic reached an N-gain value of 0.70, including in the high category and the classical percentage results of participant learning outcomes. Students reached 80.12%. The results of this research can be concluded that e-magnetic learning media based on SAC on magnetism topic at SMP Negeri 11 Gorontalo has met the criteria of being valid, practical, and effective.